Restitusi Korban Sebagai Alternatif Mitigasi Tindak Pidana Ringan (Studi Kasus Polsek Pangkalan Kerinci) - Rinaldi, Kasmanto; Ramadhani, Widia (UIR PRESS, 2021)
This study discusses the implementation of victim restitution as an alternative in solving minor criminal cases. This study aims to determine how the implementation of victim restitution as an alternative to mitigate minor crimes. The method used in this research is a qualitative method with a descriptive type r by conducting interviews with key informants and related informants. Based on the research results, it shows that the settlement of minor criminal cases by implementing restitution to the victim can be carried out if both parties agree to resolve the problem. Meanwhile, the procedure for resolving minor criminal cases is based on restorative justice that focuses on deliberation. Restitution is an obligation that must be obtained by the victim because it will ease the victim’s suffering. In the process of implementing restitution, the police acts as a mediator between the perpetrator and the victim, so the implementation runs smoothly without any obstacles. However, the implementation of restitution in minor criminal cases, especially in Pangkalan Kerinci Police Sector is not effective enough, therefore there is a need for socialization and further action to the community regarding restitution rights for victims, so the victims and community protection can be achieved.